Edukasi Strategi Metodologi Penelitian Multidisiplin untuk Penguatan Analisis Data dan Publikasi Ilmiah di Universitas Batam - Sihar Tambun; Helena Sitorus; Riris Rotua Sitorus (Jurnal Pemberdayaan Nusantara, 2026)
Mastery of mixed methods is crucial for researchers to produce high-quality research and publish their results in reputable journals. Expertise in mixed methods research is essential across various disciplines, both for research purposes, publication of research articles, and both. This workshop was conducted to meet the needs of lecturers and postgraduate students at Batam University. The methods used were lectures and practical data processing. The workshop also included practical quantitative data processing with Lisrel software and practical qualitative data processing with NVivo software. The workshop delivered excellent results. 98% of participants understood and were able to independently conduct mixed methods research, including processing research data with Lisrel and NVivo software. However, workshop participants were advised to review all workshop materials and immediately implement everything learned from this research methods workshop.